Effect of incorporation of guava leaf powder on storage stability of curd balls under aerobic packaging condition at refrigeration temperature - Vihan , Varsha; Singh, V. P.; Verma, Akhilesh K.; Umaraw, Pramila; Singh, Chirag; Verma , Shardanand (Indian Journal of Dairy Science, 2024)
The present study has undertaken the evaluation of the impact of incorporating guava leaf powder (GLP) on the storage stability of developed curd balls. Four groups of curd balls were formulated with the addition of different levels of guava leaf powder C (control without GLP), T1 (with 1.5% GLP), T2 (with 3.0% GLP), and T3 (with 4.5% GLP). The results revealed that pH and titratable acidity were significantly (P≤0.05) lower in the treated groups than in control. Peroxide value, thio-barbituric acid reactive substances, and free fatty acid content were significantly (P≤0.05) lower in GLP incorporated curd balls than in control. Guava leaf powder added to curd balls has significantly (P≤0.05) higher DPPH, ABTS, and total phenolic content than the control. Among all samples, T3 (4.5%) recorded significantly (P≤0.05) lower microbial growth than the others groups of curd balls. However, sensory panelists rated significantly (P≤0.05) higher scores for T2 than T3. The sequent of the study concluded that the curd balls prepared with the inclusion of 3.0 % guava leaf powder prevent Physico-chemical quality deterioration, improve antioxidant capacity, reduced lipid oxidation and microbial growth with acceptable sensory attributes.